Ethics conflicts from the care and die at intensive care units: percepcions of nursing students - Santana, Júlio Cesar; Sá, Ana Cristina de; Zaher, Vera Lúcia (Revista de Enfermagem UFPE on line, 2008)
ABSTRACT Objective: to understand the ethical conflicts meaning in the taking care process and perception of the nursing academics of dying in Intensive Care Units (ICUs). Method: research with phenomenological approach, according to the following scheming question: which had been the ethical conflicts lived deeply by you during the training period on ICUs. For such question, it was looked to refer the bioethical questions that contemplate the science of life. They had gotten the deposition of nine nursing academics, of which they had excited the units of meaning, making possible to investigate the citizens everyday and its expression in the world-life. Results: it had been attributed units of meanings in a perspective that emerged the ethical conflicts of academics nursing in the taking care and dying process: holistic care X technique; care centered in the illness; family influence and the communication in taking care of; ICUs limits: until when investing? Conclusion: the reflections revealed that the nursing academics face complex situations, that go, since the routines techniques learning process to diverse situations that involves the human suffering and revealing ethical conflicts of our fragility, waking up its proper human being dimension, the existential direction, sensitizing them for a taking care reflection, becoming vulnerable to the suffering and questioning the limits where they are placed in. Descriptors: ethics; nursing; students; intensive care units; bioethics. RESUMO Objetivo: compreender o significado dos conflitos éticos no processo do cuidar e do morrer em Unidades de Terapia Intensiva (UTIs) na visão dos acadêmicos de enfermagem. Métodos: pesquisa com abordagem fenomenológica, direcionada pela seguinte questão norteadora: quais os conflitos éticos vivenciados por você durante o período de estágio em UTIs? Para tal, procurou-se referenciar as questões da bioética que contemplam a ciência da vida. Resultados: foram atribuídas unidades de significado na medida em que emergiam os conflitos éticos dos acadêmicos no processo do cuidar e morrer: cuidado holístico X tecnicismo; cuidado centrado na doença; limites na UTI: até quando investir? Conclusão: as reflexões desvelaram que os acadêmicos de enfermagem enfrentam situações complexas, que vão desde o processo de aprendizagem das rotinas técnicas a situações diversas que envolvem o sofrimento humano e conflitos éticos reveladores de nossa fragilidade, despertando a sua própria dimensão humana, o sentido existencial, sensibilizando-os para uma reflexão do cuidar, tornando-os vulneráveis ao sofrimento e questionando os limites em que são colocados. Descritores: ética; enfermagem; estudantes; unidades de terapia intensiva; bioética. RESUMEN Objetivo: El comprender el significado de los conflictos éticos en el proceso de cuidar y morir en Unidades de Terapia Intensiva (UTIs), dentro de la percepción de los académicos de enfermeria. Metodos: pesquisa con embasamiento fenomenológico, direccionada por la siguiente cuestión norteadora: ¿cuales fueron los conflictos éticos vivenciados por usted durante el periodo de estagio en UTIs?” Para tal, se buscó referenciar las cuestiones da bioética que contempla la ciencia de la vida. Resultados: el final de la pesquisa fueron atribuidas unidades de significados en una perspectiva que emergían los conflictos éticos de los académicos en el proceso de cuidar y morir: cuidado holístico X tecnicismo; cuidado centrado en enfermedad; límites en UTI: ¿hasta cuando invertir? Conclusion: las reflexiones desvelaron que los académicos de enfermeria enfrentan situaciones complejas, que van, desde el proceso de aprendizaje de rutinas técnicas hasta situaciones diversas que envuelven el sufrimiento humano y conflictos éticos reveladores de nuestra fragilidad, despertando su propria dimensión humana, el sentido existencial, sensibilizándolos para una reflexión del cuidar, volviéndose vulnerables al sufrimiento y cuestionando los límites que son colocados. Descriptores: ética; enfermería; estudiantes; unidades de terapia intensiva; boética.